From crisis to resilience: Empowering communities through food security programs during the COVID-19 pandemic - Adi, Isbandi Rukminto; Qadrina, Hafizha Ilma (Journal of Socio-Cultural Sustainability and Resilience, 2025)
Background: This study discusses community empowerment activities for communities affected by the Covid-19 pandemic through the food security program in the Tenjo Village by the Human Initiative. The research approach used is a qualitative research approach with descriptive research type with a research period from October 2020 to July 2021. This study will also examine whether there are differences in the stages of community empowerment carried out before and after the Covid-19 pandemic. In addition, this study will also examine the obstacles in implementing community empowerment during the Covid-19 pandemic in the Tenjo Village food security program. Methods: The data sources used were obtained through in-depth interviews, observation and documentation studies involving seven informants. Findings: The results showed that there were four stages of empowerment held in the program, including the planning, preparation, program implementation, and activity evaluation monitoring stages. During implementation program, there are several inhibiting factors that can be classified based on organizational aspect, networking aspect, community aspect, and external aspect. To overcome the obstacles from those various aspects, efforts are made to minimize the impact of those obstacles. Conclusion: The results of the analysis show that the stages of empowerment held in the Tenjo Village food security program are in accordance with the seven stages of community development. In addition, the obstacles that occur during program implementation are in accordance with the obstacles in the community development stage. Meanwhile, the efforts made to overcome these obstacles can be done with a description in the evaluation of the process and the results of the changes. Novelty/Originality of this article: This research not only describes the stages of empowerment carried out, but also analyzes the differences in the stages of community empowerment before and after the pandemic. The focus on change and adaptation at this stage is an aspect that has not been widely explored in community empowerment research during times of crisis.